2020
DOI: 10.11604/pamj.supp.2020.35.2.23832
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of coronavirus disease 2019 (COVD-19) outbreak cases in Oyo State South West Nigeria, March-April 2020

Abstract: Introduction On March 17th, 2020, Oyo State recorded her first case of COVID-19 through a United Kingdom returnee. Oyo State Ministry of Health with the support of technical and development partners responded quickly and effectively to contain the outbreak. The outbreak was characterized by place, person and time. Methods Field investigations were conducted and contact tracing and follow up done, all confirmed cases were identified, line-listed and analyzed using Epi-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
5
10
0
Order By: Relevance
“…The epidemic curve of the outbreak suggests a propagated pattern of transmission of the disease. This is consistent with previous COVID-19 outbreak reports and studies in other regions of Nigeria NCDC [23], Usman et al, [3], Elimian et.al., [18] and in China by Chen et al, [24]. The pattern of the outbreak is suggestive of person-to-person transmission which further explains the findings in this investigation that most of the cases (88.8%) occurred in urban settings where crowded conditions, clustered settlement pattern of the houses and large-scale human interactions due to daily commercial activities could have facilitated the spread of the outbreak [25] [26].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The epidemic curve of the outbreak suggests a propagated pattern of transmission of the disease. This is consistent with previous COVID-19 outbreak reports and studies in other regions of Nigeria NCDC [23], Usman et al, [3], Elimian et.al., [18] and in China by Chen et al, [24]. The pattern of the outbreak is suggestive of person-to-person transmission which further explains the findings in this investigation that most of the cases (88.8%) occurred in urban settings where crowded conditions, clustered settlement pattern of the houses and large-scale human interactions due to daily commercial activities could have facilitated the spread of the outbreak [25] [26].…”
Section: Discussionsupporting
confidence: 93%
“…The finding in this investigation that a high proportion of the confirmed COVID-19 cases were males and between the age group of 20 to 59 years is consistent with previous studies in Oyo State, Nigeria [3] and Wuhan, China [17].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A number of studies have reported that sex differences exists in the clinical symptoms and laboratory parameters of COVID-19 patients and obvious abnormalities have been seen among males compared to females [19][20][21]. Researchers have also observed a higher mortality from corona virus disease among males compared to females [22].…”
Section: Introductionmentioning
confidence: 99%